If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 12) = 27 * 6 + -12 Reorder the terms: 2(12 + x) = 27 * 6 + -12 (12 * 2 + x * 2) = 27 * 6 + -12 (24 + 2x) = 27 * 6 + -12 Multiply 27 * 6 24 + 2x = 162 + -12 Combine like terms: 162 + -12 = 150 24 + 2x = 150 Solving 24 + 2x = 150 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 2x = 150 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = 150 + -24 2x = 150 + -24 Combine like terms: 150 + -24 = 126 2x = 126 Divide each side by '2'. x = 63 Simplifying x = 63
| -5/3(y-10)-1/4y= | | -5/3(y-10)-1/4y | | 6d+25=-5 | | 80=2r-7(11) | | 6x+3-72x=0 | | 0=-4w-31 | | (5x/x^5) | | [0.2*ln(580-Y)]+[0.8*ln(180-Y)]=ln(200) | | 10+3n=35 | | x^2+y^2-12x+4=0 | | 0=-48v+161 | | 4.2=x-83.5 | | 6t+3(1-3t)= | | 8(t-1)=6(t+3) | | 3x-2=4x+15 | | -5(x+2)-4=-29 | | Ad=12ax+14 | | n(n+1)(n-1)(n-2)=840 | | 1=g/2-2 | | (10n)3/2 | | 0=-5x-(625/10) | | -5=5-2d | | -w/3=12 | | 2B-11=88 | | -4/7x=16/27 | | 2v+1=10 | | 2x^2+2x+75=0 | | y/4=14 | | (2+w)(4w-5)=0 | | 20x-23=7 | | 6(X+5m+4)= | | 9=5+2t |